Need Analysis for Listening Skill Development for Undergraduate Students - Enis Fitriani; Yahmun Yahmun; Marsuki Marsuki (IKIP Budi Utomo Malang, 2021)
Innovation in teaching listening is urgently needed. This study resulted the questionnaire survey of students’ needs of listening subject. These results were compared to the students’ mid-term results and Basic Listening learning outcomes. The survey was completed by 100 first-year English Education students. The analysis and comparison were objected to find out the answers of these questions: what barriers obstructed the progress of the students’ listening skill? And what were the students’ listening skills needs? The study found that there is an interstice between students’ needs and the learning got in relating to listening comprehension. Hence, this study expected that the its findings can help to grant preferable understanding of the students’ needs and developing the curriculum properly.